1984
DOI: 10.1177/106002808401800102
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Management of Primary Dysmenorrhea

Abstract: Primary dysmenorrhea is a common gynecologic disorder. Dysmenorrheic pain normally has an onset of from 2-12 hours before the start of menses and tapers over the next one to two days. Although the exact etiology is unknown, this condition is associated with an increase in prostaglandin F2 alpha. In the past, nonspecific treatments such as heat and exercise were tried, with poor results. Little relief was offered by antispasmodics or low-dose aspirin. Currently, effective therapy for primary dysmenorrhea includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Dysmenorrhea is directly related to elevated level of prostaglandin F 2 (PGF 2 ) and is typically treated with drugs that inhibit synthesis of prostaglandins in the USA (Wenzloff & Shimp 1984). In Taiwan, paracetamol (panadol/acetaminophen) is one of the popular over-the-counter Western medicines and it is known as an analgesic as are the NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…Dysmenorrhea is directly related to elevated level of prostaglandin F 2 (PGF 2 ) and is typically treated with drugs that inhibit synthesis of prostaglandins in the USA (Wenzloff & Shimp 1984). In Taiwan, paracetamol (panadol/acetaminophen) is one of the popular over-the-counter Western medicines and it is known as an analgesic as are the NSAIDs.…”
Section: Discussionmentioning
confidence: 99%
“…While 47-70% of university students use analgesics for pain relief (Cronje and Kritzinger, 1991;Polat et al, 2009;Ortiz, 2010), 30% of adolescents do not use over-the-counter medications to treat their menstrual pain and only 18% use prescription medication (Wenzloff and Shimp, 1984;Campbell and McGrath, 1997;O'Connell et al, 2006), although the perceived effectiveness of pharmacological methods in the treatment of menstrual discomfort is superior to that of nonpharmacologic methods. In a questionnaire-based study of 289 female adolescents, 98% reported using no less than one non-pharmacologic method to control menstrual discomfort.…”
Section: Treatment Of Primary Dysmenorrheamentioning
confidence: 99%
“…Dysmenorrhoea is directly related to elevations in prostaglandin F2 (PGF2). It is typically treated with drugs that inhibit prostaglandins in the USA (Wenzloff & Shimp 1984). In Taiwanese culture, less emphasis is placed on western medications than on age-old cultural treatments, i.e., TCMs.…”
Section: Frequency and Distribution Of Medications Used By Taiwanese mentioning
confidence: 99%